School Well-Being Siswa Sekolah Dasar dan Siswa Sekolah Menengah Pertama Pengguna Sistem Full-Day School di Indonesia - Faizah, Faizah; Rahma, Ulifa; Dara, Yuliezar Perwira; Gunawan, Candra Laksmana (Jurnal Kajian Bimbingan dan Konseling, 2020)
Character building education in Indonesia has officially become a new regulation in the aspect of education therefore several state-owned schools have implemented a full-day system. The school system and the presence of student are complementary components, students' perspective upon themselves and the school environment as part of well-being fulfillment. The purpose of this study was to determine the state of school well-being of elementary school students and junior high school students who implemented the full-day system. This research was a comparative quantitative study with accidental sampling technique. This research was conducted in Malang, involving 285 students from five elementary schools and 275 students from three junior high schools as participants. The research instrument used was the School Well-being Profile (SWP). The data analysis using independent two-sample t-test with Welchs t-test method. The results showed there were differences in school well-being in elementary and junior high school students in full-day systems. Elementary students have higher school well-being compared to junior high school students. Furthermore, the results of this study can be used as a reference to provide counseling services in improving school well-being of full day school students, especially junior high school students.